Integrating data from spontaneous and induced trans-10 shift of ruminal biohydrogenation reveals discriminant bacterial community changes at the OTU level - Enjalbert, Francis; Zened, Asma; Cauquil, Laurent; Meynadier, Annabelle (Frontiers in Microbiology, 2023)
Introduction Microbial digestion is of key importance for ruminants, and disturbances can affect efficiency and quality of products for human consumers. Ruminal biohydrogenation of dietary unsaturated fatty acids leads to a wide variety of specific fatty acids. Some dietary conditions can affect the pathways of this transformation, leading to trans-10 fatty acids rather than the more usual trans-11 fatty acids, this change resulting in milk fat depression in dairy cows. Materials and methods We combined data from an induced and spontaneous trans-10 shift of ruminal biohydrogenation, providing new insight on bacterial changes at different taxonomic levels. A trans-10 shift was induced using dietary addition of concentrate and/or unsaturated fat, and the spontaneous milk fat depression was observed in a commercial dairy herd. Results and discussion Most changes of microbial community related to bacteria that are not known to be involved in the biohydrogenation process, suggesting that the trans-10 shift may represent the biochemical marker of a wide change of bacterial community. At OTU level, sparse discriminant analysis revealed strong associations between this change of biohydrogenation pathway and some taxa, especially three taxa belonging to [Eubacterium] coprostanoligenes group, Muribaculaceae and Lachnospiraceae NK3A20 group, that could both be microbial markers of this disturbance and candidates for studies relative to their ability to produce trans-10 fatty acids.